2016
DOI: 10.1002/ange.201510609
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Shell Mediated Power Density Independent Orthogonal Excitations–Emissions Upconversion Luminescence

Abstract: Lanthanide doped core-multishell structured NaGdF 4 :Yb,Er@NaYF 4 :Yb@NaGdF 4 :Yb,Nd@NaYF 4 @-NaGdF 4 :Yb,Tm@NaYF 4 nanoparticles with power-density independent orthogonal excitations-emissions upconversion luminescence (UCL) were fabricated for the first time.T he optical properties of these core-multishell structured nanoparticles were related to the absorption filtration effect of the NaGdF 4 :Yb,Tm layer.Bytuning the thickness of the filtration layer,t he nanoparticles can exhibit unique two independent gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In brief, the CSUC emission intensity, Iem, is proportional to the power n of the NIR excitation power (P NIR), n is the number of Yb 3+ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 When the concentration of Yb 3+ ions is adjusted at the same level (normalized with the same absorbance of Yb 3+ ions), Iem can be written as I'em∝N 1.29 Yb (the calculation details were shown in Supporting Information). Theoretically, the CSUC emission intensity of NaYF4:40%Tb,Yb@CaF2 with different doping concentrations of Yb 3+ ions (20,40 and 60 %) should enhance at least 1-, 2.44-or 4.13-fold, which agrees with the experimental results of 1-, 2.2-and 4.6-fold shown in Figure 4a. The slight differences between the theoretical inference and the experimental data was probably caused by the average distance reduction between the Yb 3+ and Tb 3+ ions, which influences the cooperative energy transfer efficiency.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In brief, the CSUC emission intensity, Iem, is proportional to the power n of the NIR excitation power (P NIR), n is the number of Yb 3+ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 When the concentration of Yb 3+ ions is adjusted at the same level (normalized with the same absorbance of Yb 3+ ions), Iem can be written as I'em∝N 1.29 Yb (the calculation details were shown in Supporting Information). Theoretically, the CSUC emission intensity of NaYF4:40%Tb,Yb@CaF2 with different doping concentrations of Yb 3+ ions (20,40 and 60 %) should enhance at least 1-, 2.44-or 4.13-fold, which agrees with the experimental results of 1-, 2.2-and 4.6-fold shown in Figure 4a. The slight differences between the theoretical inference and the experimental data was probably caused by the average distance reduction between the Yb 3+ and Tb 3+ ions, which influences the cooperative energy transfer efficiency.…”
Section: Introductionsupporting
confidence: 85%
“…Different from common upconversion systems with activators such as Er 3+ ( Figure S8), Tm 3+ and Ho 3+ that have a microsecond level lifetime, NaYbF4:Tb@CaF2 possesses a much longer upconversion emission lifetime, which will result in a promising application of time-resolved luminescence. 33,[38][39][40][41] We explored the optimized doping concentration of Tb 3+ ions. The TEM images of NaYbF4:Tb@CaF2 nanoparticles doped with y% Tb 3+ ions (y = 10, 20, 30, 40, 50, 60 and 70) are shown in Figure S9, and the CSUC emission Fluorescence decay curves of (b) Tb 3+ emission at 541 nm ( 5 D 4 → 7 F 5 ) and (c) Yb 3+ emission at 975 nm ( 2 F 5/2 → 2 F 7/2 ) from NaYbF 4 :40%Tb@CaF 2 , NaYbF 4 :40%Tb@CaF 2 :20%Yb and NaYbF 4 :40%Tb@CaF 2 :20%Tb nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Thec ore-multishell structured NaGdF 4 :Yb,Tm-@NaYF 4 @N aGdF 4 :Nd@NaYF 4 U/DCNPs were fabricated and employed to functionalize the polymer nanocapsules (Supporting Information, Figure S2). [36,37] In this nanostructure,T m 3+ doped nanoparticles were constructed as core for emission of UV/Vis upconversion luminescence under 980 nm excitation. TheN aGdF 4 :Nd layer can emit downconversion NIR-II fluorescence under 800 nm excitation for downconversion bio-imaging.T ransmission electron microscopy (TEM) and the high-angle annular dark-field scanning TEM (HAADF-STEM) images ( Figure 2A)o ft he as-prepared U/DCNPs show discernible contrast for the multi-layer structure with au niform diameter of about 20 nm.…”
mentioning
confidence: 99%
“…Recently, considerable efforts have been devoted to developing novel upconversion nanoparticles excited by 808 nm laser. It was found that the Nd 3+ -sensitized upconversion nanoparticles exhibited efficient upconversion luminescence (UCL) under the excitation of 808 nm laser, in which Nd 3+ featured a sharp absorption band at 808 nm and acted as sensitizer [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, the energy transfer from Nd 3+ to Yb 3+ to Er 3+ was expected to realize high-efficiency UCL with low heating effect and deep penetration under the excitation of 808 nm laser.…”
Section: Accepted Manuscriptmentioning
confidence: 99%